A critical cartography of domestic violence policies in Mozambique - Eunice Jethá; Ines Keygnaert; Mohamed Seedat; Joaquim Nhampoca; Mohsin Sidat; Kristien Roelens (BMC, 2021)
Plain language summary Domestic violence (DV) which involves physical, sexual and psychological threats, is a Mozambican public health problem that compromises the quality of life of the victims and their families. In extreme cases, such abuse can result in fatalities. In response to DV, the Mozambican government has adopted international treaties and conventions to design national DV prevention and containment policies and laws. This article aims to describe how national policies, laws and strategic plans define DV, and align with international treaties and conventions as well as with each other. The analysis indicates that the country's policies, laws and strategic plans do not meet all recommendations of international guidelines. These include those proposed by the United Nations (UN) and the Pan American Health Organization (PAHO). While strategic plans propose measures directed at preventing the occurrence of DV and providing victim assistance, they make no reference to monitoring and evaluation, data management and advocacy. Given these mixed findings it is proposed that synergy be obtained among legislation, policy and strategic planning documents and that these documents be revised to incorporate a focused multisectoral approach and monitoring and evaluation.